If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6c + -8 = 10c + 7 Reorder the terms: -8 + 6c = 10c + 7 Reorder the terms: -8 + 6c = 7 + 10c Solving -8 + 6c = 7 + 10c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-10c' to each side of the equation. -8 + 6c + -10c = 7 + 10c + -10c Combine like terms: 6c + -10c = -4c -8 + -4c = 7 + 10c + -10c Combine like terms: 10c + -10c = 0 -8 + -4c = 7 + 0 -8 + -4c = 7 Add '8' to each side of the equation. -8 + 8 + -4c = 7 + 8 Combine like terms: -8 + 8 = 0 0 + -4c = 7 + 8 -4c = 7 + 8 Combine like terms: 7 + 8 = 15 -4c = 15 Divide each side by '-4'. c = -3.75 Simplifying c = -3.75
| -[5x-(3x+2)]=-3-[3(2x-4)-2x] | | 8x+5y=840 | | 5x+6+8x-15+x=180 | | 6+2y-8=13 | | QS=C+dp | | 1/5(15+5)=8n-9 | | 2/3(2x-3)=12 | | 22=-2y-12 | | 17-8b=3b | | w-3=8 | | 11-11= | | 9a=7z-8 | | (1-2b)/(b-2)=(b+2)/(1+2b) | | n+.2n=30 | | 79x-50=252 | | -45y=126-27y | | 9a-7a+4a= | | 0=15x-1/2(10)x^2 | | 21=2h-18 | | 9a+7a-4a= | | -7x-0=-6 | | 14y=13(y+15) | | 4y=13(y+15) | | 4(a+3)+1=2(a+3)+2a+6 | | 1-3(x-3)=4x+3 | | 14w-19w=35 | | x^2+v=w | | (x-3)*31= | | 0.02(5x-4)=0.03(x-3)+0.05 | | -7x=-6 | | x-2*31= | | 31*(x-2)= |